2005
DOI: 10.1104/pp.104.056010
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Suppression of a (+)-δ-Cadinene Synthase Gene in Cotton Prevents the Induction of This Defense Response Gene during Bacterial Blight Infection But Not Its Constitutive Expression  

Abstract: In cotton (Gossypium hirsutum) the enzyme (1)-d-cadinene synthase (CDNS) catalyzes the first committed step in the biosynthesis of cadinane-type sesquiterpenes, such as gossypol, that provide constitutive and inducible protection against pests and diseases. A cotton cDNA clone encoding CDNS (cdn1-C4) was isolated from developing embryos and functionally characterized. Southern analysis showed that CDNS genes belong to a large multigene family, of which five genomic clones were studied, including three pseudoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 69 publications
2
76
0
3
Order By: Relevance
“…The resulting metabolites are modulated by other enzymes which are induced by environmental stress factors. Little is known about the specific mechanisms in fungi but from plants several environmental factors, including UV-radiation (Back et al 1998), infection (Townsend et al 2005) and herbivore attack (Yuan et al 2008), have been identified which lead to the enhanced production of volatile sesquiterpenes.…”
Section: Volatile Sesquiterpenes From Fungimentioning
confidence: 99%
“…The resulting metabolites are modulated by other enzymes which are induced by environmental stress factors. Little is known about the specific mechanisms in fungi but from plants several environmental factors, including UV-radiation (Back et al 1998), infection (Townsend et al 2005) and herbivore attack (Yuan et al 2008), have been identified which lead to the enhanced production of volatile sesquiterpenes.…”
Section: Volatile Sesquiterpenes From Fungimentioning
confidence: 99%
“…Gossypol is one of the most important sesquiterpene phytoalexin, which exists specifically in cotton and plays a crucial role in the defense against the invasion of pathogens and insects (20). Though many phytoalexin-related genes have been shown to be important in mediating cotton defense, the molecular mechanism is unknown (21,22). As sequencing technology develops, a number of genes related to disease resistance (e.g.…”
mentioning
confidence: 99%
“…Most research has focused on the biosynthesis of gossypol and its important role in cotton growth, so that although cotton pigment glands have attracted the attention of researchers for a number of years, the molecular mechanism of their formation is unknown (Luo et al 2001;Townsend et al 2005;Xu et al 2004). Our group has been researching the molecular mechanism of cotton pigment gland formation.…”
Section: Discussionmentioning
confidence: 99%
“…Most cotton plants and seed contain pigment glands that produce gossypol, which is an important deterrent against a wide variety of pests and microbial pathogens Townsend et al 2005). Cotton could also become one of the largest sources of edible oilseed and also be a source of relatively high-quality protein (Sunilkumar et al 2006;Bertrand et al 2005;Gerasimidis et al 2007); however, cottonseed is an underutilised food or feed source due to the presence of gossypol, a terpenoid aldehyde that is toxic to non-ruminant animals and humans (Sang et al 1980;Shandilya et al 1982;Weinbauer et al 1983;Heywood 1988;Du et al 2004;Stipanovic et al 2006).…”
Section: Introductionmentioning
confidence: 99%